A global bibliometric and visualized analysis in the status and trends of corneal tissue engineering research from 1991 to 2021. (November 2022) - Niu, Hua-Qing; Yang, Yun; Wang, Bei-Bei; Xiao, Wen-Tian; Wu, Hui-Ru; Liu, Ya-Dong; Zheng, Bo-Wen; Zou, Ming-Xiang
Corneal tissue engineering has developed rapidly in recent years, with a large number of publications emerging worldwide. This study focused on exploring the global status and research trends in this field. Publications related to corneal tissue engineering from 1991 to 2021 were acquired from the Science Citation Index-Expanded (SCI-Expanded) of Web of Science (WoS). Firstly, the VOS viewer software was chosen for visualizing bibliometric networks, including bibliographic coupling analysis, co-citation analysis, co-authorship analysis, and co-occurrence analysis, and the CiteSpace software was used to detect burst keywords. Subsequently, the publication trends in corneal tissue engineering research were also predicted. In present study, 953 publications were selected and analyzed. The number of annual publications was increasing globally and was predicted to continue the current trend. While Japan ranked top 1 in terms of average citation, the USA contributed the most to the corneal tissue engineering research with highest number of citations and highest H -index. The journal of Biomaterials contributed the largest publication number. The top-ranked institutions were National University of Singapore and Singapore National Eye Center. Additionally, researches could be manually divided into four clusters: "biomaterial related research, " "cell related research, " "transplantation therapy, " and "mechanism research on biomaterials." Specifically, the research topic "hydrogel" was predicted to be hotspots which may help researchers to explore new directions for future research.